1981
DOI: 10.1177/030089168106700505
|View full text |Cite
|
Sign up to set email alerts
|

Defective Function of Granulocytes in Patients with Cancer

Abstract: Mobilization of granulocytes into a serum-filled chamber, histochemical nitroblue tetrazolium (NBT) reduction tests, and phagocytosis were performed in 11 patients with solid tumors treated with surgical excision and chemotherapy and in 22 untreated or surgically treated patients. The results revealed a decreased mobilization (p less than 0.001) and an impaired capability of neutrophils to reduce NBT after stimulation (p less than 0.05) in both groups of patients. The decrease in the values in the stimulated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, the PMN can show a generalized defect in the ability to mobilize in patients with proliferative hematological disease337–342 and solid tumors 343–345. They may also show a reduction in oxidative metabolism in solid tumors345–351 and also in leukemias 346, 352–354. PMN from patients with gynecological cancer may show a reduced production of the superoxide anion 355.…”
Section: Does Defective Pmn Function Encourage the Growth Of A Canmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the PMN can show a generalized defect in the ability to mobilize in patients with proliferative hematological disease337–342 and solid tumors 343–345. They may also show a reduction in oxidative metabolism in solid tumors345–351 and also in leukemias 346, 352–354. PMN from patients with gynecological cancer may show a reduced production of the superoxide anion 355.…”
Section: Does Defective Pmn Function Encourage the Growth Of A Canmentioning
confidence: 99%
“…PMN from patients with gynecological cancer may show a reduced production of the superoxide anion 355. Further, the phagocytic capacity of PMN can be strongly reduced in patients with leukemia or lymphoma,356–363 in patients with bone marrow metastasis,364 in patients with urogenital cancer,365 and other solid tumors,345 and in patients with myeloma 340. In addition, many authors have reported a diminished bactericidal or candidacidal capacity of PMN in patients with hematological cancer352, 362, 366–371 and in those with solid tumors,296, 366, 367 and a reduced cytostatic or cytotoxic activity against cancer cells compared to PMN from normal donors 20, 34…”
Section: Does Defective Pmn Function Encourage the Growth Of A Canmentioning
confidence: 99%
“…15 Defects in the neutrophil cytotoxic oxidative metabolism have been found with increased incidence in patients with lung cancer 16 and other solid organ diseases. 15 Similarly, the associations between defective leukocyte chemotaxis and motility and melanoma, 17 breast cancer, 18 and colon cancer 19 have been demonstrated. Furthermore, there has long been evidence that cancer tumors produce factors that inhibit neutrophil function.…”
Section: Discussionmentioning
confidence: 90%
“…[15] Defects in neutrophil cytotoxic oxidative metabolism have been found with increased incidence in patients with lung cancer[16] and other solid organ diseases [15]. Similarly, association between defective leukocyte chemotaxis and motility and melanoma [17], breast cancer [18], and colon cancer [19] have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%